2020
DOI: 10.1007/s00415-020-10125-w
|View full text |Cite
|
Sign up to set email alerts
|

Early discrimination of cognitive motor dissociation from disorders of consciousness: pitfalls and clues

Abstract: Bedside assessment of consciousness and awareness after a severe brain injury might be hampered by confounding clinical factors (i.e., pitfalls) interfering with the production of behavioral or motor responses to external stimuli. Despite the use of validated clinical scales, a high misdiagnosis rate is indeed observed. We retrospectively analyzed a cohort of 49 patients with severe brain injury admitted to an acute neuro-rehabilitation program. Patients' behavior was assessed using the Motor Behavior Tool and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 46 publications
0
20
1
1
Order By: Relevance
“…Recently, several studies have shown that the Motor Behavioral Tool (MBT) might reveal residual cognition in patients diagnosed as VS by the CRS-R [46,47]. The MBT has been found unaffected by the presence of pitfalls that interfere with sensory and motor afferents (e.g., polyneuropathy, myopathy, myelopathy, and aphasia) or intrinsic brain activity (e.g., epilepsy) [48]. Future studies should therefore further investigate this tool and demonstrate its ability to detect CMD at the bedside, as it might represent a critical clinical tool for clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have shown that the Motor Behavioral Tool (MBT) might reveal residual cognition in patients diagnosed as VS by the CRS-R [46,47]. The MBT has been found unaffected by the presence of pitfalls that interfere with sensory and motor afferents (e.g., polyneuropathy, myopathy, myelopathy, and aphasia) or intrinsic brain activity (e.g., epilepsy) [48]. Future studies should therefore further investigate this tool and demonstrate its ability to detect CMD at the bedside, as it might represent a critical clinical tool for clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Because the CRS-R assesses consciousness only indirectly, by way of eliciting behavioral responses to perceived stimuli, it is intrinsically vulnerable to confounders interfering with sensory perception and volitional behavioral control, even under the best of circumstances [ 34 ]. For our cohort, given the nearly universal presence of obvious confounders to select CRS-R subscales, we opted to use the CRS-R TS as a global measure of performance, with a score cutoff of 8 serving as a proxy for diagnosis of MCS.…”
Section: Methodsmentioning
confidence: 99%
“…2) and decreased anesthetic levels, gradually reducing the concentration to 0%. We analyzed cortical activity and motor behavior in detail, thus deploying measures used to follow recovery of a conscious state in humans 21,22 to follow emergence from anesthesia in mice. Motor cortex activity was measured using bilateral electrodes to record local field potentials (LFPs) during anesthetic reduction ( Fig.…”
Section: Resultsmentioning
confidence: 99%